2017
DOI: 10.1016/s1473-3099(16)30472-8
|View full text |Cite
|
Sign up to set email alerts
|

Adapting to the global shortage of cholera vaccines: targeted single dose cholera vaccine in response to an outbreak in South Sudan

Abstract: Shortages of vaccines for epidemic diseases, such as cholera, meningitis, and yellow fever, have become common over the past decade, hampering efforts to control outbreaks through mass reactive vaccination campaigns. Additionally, various epidemiological, political, and logistical challenges, which are poorly documented in the literature, often lead to delays in reactive campaigns, ultimately reducing the effect of vaccination. In June 2015, a cholera outbreak occurred in Juba, South Sudan, and because of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 18 publications
0
38
0
Order By: Relevance
“… 10 Available vaccines are licensed as two-dose regimens, although single-dose regimens have been tested and suggested as a possibility in outbreaks or when vaccine supply is low. 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 Available vaccines are licensed as two-dose regimens, although single-dose regimens have been tested and suggested as a possibility in outbreaks or when vaccine supply is low. 11 …”
Section: Introductionmentioning
confidence: 99%
“…12 Gavi, The Vaccine Alliance, later committed to fund up to 70 million doses (about US$1·85 per dose) from 2014 to 2018 to expand the support for vaccination in emergency and non-emergency (hotspot) settings through the stockpile. 11 These stockpiles, combined with the WHO prequalification of a low-cost vaccine (Shanchol; Shantha Biotechnics, Hyderabad, India) in 2011, paved the way for expanded access and increased use of the vaccine. Although travellers to cholera-prone areas commonly use kOCVs, 13 most of the world's supply of kOCV is managed and deployed through these stockpiles.…”
Section: Introductionmentioning
confidence: 99%
“…1,10,11 Furthermore, recent cholera outbreaks, such as those in Somalia, Ethiopia, South Sudan, and Yemen, have devastated communities already suffering from drought, conflict, and famine, highlighting the necessity of a robust and swift response to diarrheal disease in the context of humanitarian emergencies. 12,13 The most important step in diarrhea management for both children and adults remains appropriate rehydration based on the severity of dehydration; yet rapid and accurate assessments of the degree of dehydration in patients with diarrhea remain challenging. Multiple studies have found that clinical impression, laboratory studies, and individual physical examination signs are not accurate or reliable indicators of dehydration in patients.…”
Section: Introductionmentioning
confidence: 99%
“…1 Katja Deterding and colleagues 1 reported that a short duration of direct-acting antiviral agents, a ledipasvir plus sofosbuvir fixed-dose combination for 6 weeks, achieved a sustained virological response 12 weeks after the end of treatment in 100% of patients (n=20) with acute hepatitis C virus (HCV) genotype 1 monoinfection. However, only two patients in the study had high baseline viral loads (>1 000 000 IU/mL) and most patients (n=15) had baseline viral loads lower than 100 000 IU/mL.…”
Section: Short Duration Of Direct-acting Antivirals For Acute Hcv Infmentioning
confidence: 99%